Inovasi E-Government Dalam Perencanaan Pembangunan Daerah - Neneng Sri Rahayu (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2019)
The implementation of e-government in DKI Jakarta Province has begun since 2001 which then gave rise to the concept of Jakarta Smart City public services. One of the uses of this concept is in regional development planning of DKI Jakarta Province through the e-musrenbang application. The research method used in this study a qualitative approach. Data collection through interviews and reviewing document. Based on the results of the analysis and research conducted, it can be concluded that the implementation of e-musrenbang in the DKI Jakarta Provincial Government, Especially in the Kebon Kacang Kelurahan Office as a whole has been going well (effectively) and has been able to accommodate the aspirations of the community even though there are still shortcomings in the implementation process. In an effort to optimize the implementation of electronic development planning meetings or e-musrenbang at the Provincial Government of DKI Jakarta, the process of input, output and outcome should be considered more and further policies are needed for the Provincial Regulation of DKI Jakarta Province Number 14 of 2011 concerning Planning, Development and Integrated Budgeting, can be in the form of Regulations or Decrees of Governors governing the e-musrenbang system.